A multi-mics exploration of programmed cell death in non-obstructive azoospermia: identifying TLR4 as a central regulator and therapeutic target - Yu, Qi; Yang, Qingtao; Yuan, Shiwang; Zhao, Yili; Li, Wei; Qiao, Jun; Sun, Fa; Li, Tao (Frontiers in Cell and Developmental Biology, 2026)
BackgroundMale infertility (MI) is a globally recognized public health challenge, affecting approximately 18% of men of reproductive age worldwide. Non-obstructive azoospermia (NOA) is a major cause of NOA and is associated with dysregulated programmed cell death (PCD). However, the precise role and mechanisms of PCD in the pathogenesis of NOA remain poorly understood.MethodsIn this study, target genes associated with both PCD and NOA were retrieved from multiple public databases. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were then performed to explore underlying mechanisms. Subsequently, protein-protein interaction (PPI) network analysis identified hub genes within the network. Mendelian randomization (MR) analysis was further conducted to establish a causal relationship between key genes and NOA susceptibility. Thereafter, in vitro cell and molecular biology experiments validated the impact of the pathogenic gene on LPS-induced GC-1 spg (ts) cell injury. Finally, we queried the Comparative Toxicogenomics Database (CTD) to identify environmental exposures and natural bioactive products targeting the pathogenic gene, followed by molecular docking analysis to confirm their interactions.ResultsOur analysis identified 150 PCD-related genes that were dysregulated in NOA. GO and KEGG enrichment analyses indicated that these targets primarily regulate cell death, senescence, inflammation, oxidative stress, and various biosynthetic processes. PPI analysis identified 10 hub genes: HIF1A, TLR4, MDM2, GPX4, SNCA, MTOR, CSNK2A2, ATG5, CTSS, and PIK3CA. Subsequent MR analysis established TLR4 as being causally associated with an increased risk of NOA. In vitro experiments confirmed the involvement of TLR4 in LPS-induced damage to GC-1 spg (ts) cells. Finally, CTD database screening and molecular docking analyses identified 8 common environmental pollutants and 9 natural active products that potentially target TLR4, thereby influencing the initiation and progression of NOA.ConclusionThis study advances the understanding of PCD in the pathogenesis of NOA. It identifies and underscores the critical role of the core PCD-related gene TLR4 in NOA development, highlighting the necessity for strategies aimed at mitigating its negative impact on fertility.